Pengaruh PDRB, Pendidikan dan Struktur Tenaga Kerja Terhadap Kemiskinan di Provinsi Bali - Sudiana, I Wayan; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
This study aims to analyze the influence of regional gross domestic product, education and the structure of the agricultural labor force to the level of poverty in the province of Bali. Data sourced from BPS Bali province, the analysis technique used in this study is multiple regression analysis. The results of the analysis is based on four variables simultaneously shows the influence GDP, education and the structure of the agricultural labor force to the level of poverty in the province of Bali. T test revealed that there is a significant negative effect on poverty but in Bali, while the structure of the agricultural labor force partially influence pisitif but not signipikan against poverty in Bali
Keywords: regional gross domestic product; the education; the structure of the agricultural labor force; poverty